2019
DOI: 10.1016/j.elspec.2017.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Imaging XPS for industrial applications

Abstract: Imaging XPS has been available on commercial XPS instruments since the 1990's, however its exploitation in the elucidation of surface chemistry has been minimal due to historical limitations in spatial resolution and acquisition times. Major developments in both instrumentation and multivariate data analysis techniques have improved greatly on all these aspects and herein a range of imaging analysis to illustrate the power of XPS imaging to a diverse range of industrial sectors is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 74 publications
0
18
0
Order By: Relevance
“…XPS imaging has also recently been deployed to study corrosion phenomena of Ni−Cr−Mo alloys 8 and demonstrated to be useful for several industrial applications (such as catalysis processes, biological arrays characterization, etc.). 9 It is worth noting that there are two main methods to perform XPS imaging. 10 The first one consists of acquiring spectra by scanning an X-ray probe over the sample surface and the second one is known as parallel imaging and consists in acquiring a series of energy-filtered images incremented on energy (by using a spherical mirror analyzer 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…XPS imaging has also recently been deployed to study corrosion phenomena of Ni−Cr−Mo alloys 8 and demonstrated to be useful for several industrial applications (such as catalysis processes, biological arrays characterization, etc.). 9 It is worth noting that there are two main methods to perform XPS imaging. 10 The first one consists of acquiring spectra by scanning an X-ray probe over the sample surface and the second one is known as parallel imaging and consists in acquiring a series of energy-filtered images incremented on energy (by using a spherical mirror analyzer 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Both peaks are located at ~396.8 eV which is the energy widely attributed to Al-N bond [9,17,[31][32][33]. The subpeak at ~400 eV is ascribed to C-NH2 bonds (Figure 7).…”
Section: X-ray Photoelectron Spectroscopy (Xps) Datamentioning
confidence: 96%
“…The corrosion morphology of specimen was observed by scanning electron microscope (SEM, S4800, Japan) and the electron gun acceleration voltage was 10 kV. X-ray photoelectron spectroscopy (XPS) was obtained using a Shimadzu-Kratos AXIS Ultra DLD with Al Kα as excitation source, and the binding energy was calibrated by ± 0.1 eV C1 s peaking at 284.6 eV [27]. The three-dimensional morphology of steel surface was observed using Olympus.…”
Section: Surface Characterizationmentioning
confidence: 99%